(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This article provides detailed information about the spread of Islam and the formation of the madrasa education system in the Movarounnahr region. The influence of Islam on local culture and social life, its role in the development of science and education is considered. At the same time, the importance of madrasahs as scientific centers and the changes that took place in social and cultural life through them are analyzed.